2020
DOI: 10.18662/po/11.1sup1/127
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Group as an Educational Platform for Foreign Language Acquisition

Abstract: In the research the educational potential of Facebook for language acquisition is studied. The methodological experiment and survey were conducted aimed at studying the efficiency of Facebook-assisted teaching in the Facebook group for the development of students' vocabulary, listening and writing skills. Quantitative and qualitative analysis, observation, interpretation, control and measuring were applied in the research. The Facebook group was viewed as an educational environment where a set of specially org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Undoubtedly, the possibilities of social networks and digital technologies are open to further research direction. Several studies that have considered the role of Facebook and Twitter in the study of foreign languages (GIACHANOU, CRESTANI, 2016;MYKYTIUK et al 2020), shows that the effectiveness of such application is quite high and expressed in increased academic performance, greater motivation, students approve of the use of such interactive learning tools. The conducted gamma study also confirms this hypothesis, more than 80% of students responded positively to the active use of interactive technology, increased their presence on online platforms, making more intense their foreign language lessons.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the possibilities of social networks and digital technologies are open to further research direction. Several studies that have considered the role of Facebook and Twitter in the study of foreign languages (GIACHANOU, CRESTANI, 2016;MYKYTIUK et al 2020), shows that the effectiveness of such application is quite high and expressed in increased academic performance, greater motivation, students approve of the use of such interactive learning tools. The conducted gamma study also confirms this hypothesis, more than 80% of students responded positively to the active use of interactive technology, increased their presence on online platforms, making more intense their foreign language lessons.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of using virtuality, social networks and media platforms in the process of forming linguistic competence is being developed separately (MYKYTIUK, 2020;TASHAKORI, HAGHIGHAT, 2019); the importance of an integrated approach to the educational process, as well as the formation of professional competencies has been determined (SALGUR, 2013;HOWARD-JONES, 2014); multimedia tools and digital technologies as platforms with wide educational opportunities have been also considered (POLAND, at al, 2003). Problems of maintainability of education have been developed, forasmuch as this aspect also requires from the teacher constant improvement of knowledge and skills (SIM, POP, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysis of the researches has shown that modern technologies for foreign language learning and teaching are rather effective. For example, the study of Facebook with educational purposes (Kabilan & Zahar, 2016;Kostikova et al, 2019;Mykytiuk et al, 2020;Sim & Pop, 2014) has demonstrated that social networks not only developed different language skills but also encouraged the students' learning. Moreover, modern educational technologies are able to engage students in the language learning and keep their interest (Tashakori & Haghighat, 2019).…”
Section: Experience Comparisonmentioning
confidence: 99%